PENDEKATAN HERMENEUTIKA AL-QURAN KONTEMPORER NASHR HAMID ABU ZAID - Ahmad Zayyadi (Fakultas Ushuluddin Adab dan Humaniora (FUAH), Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2017)
The controversial thoughts of Nasr Hamid Abu Zayd provide enough variation and inspiration for the development of religious thought, especially regarding the hermeneutical theory applied in the gender discourse and women discussed in this article. In general, his hermeneutical theory of Abu Zayd is more critical of the study of the Qur'an as a